War, technology, and environmental destruction: An ecocritical reading of Ghost Fleet - Dwi Linda Kusuma; Azyyati, Nurina (Alphabet, 2025)
Environmental issues are currently a global focus, affecting various aspects of life, including literature. Some contemporary literary works, such as Ghost Fleet, a novel by P.W. Singer and August Cole, also engage with environmental issues. Ghost Fleet is a contemporary techno-thriller that explores the possibility of a third World War, emphasizing the use of sophisticated and cyber technologies in warfare. Although ecological issues are not the novel’s main topic, its depiction of nature as a background highlights the significant role of war and technology on environmental destruction. With that background, this study examines these issues by using the lens of ecocriticism, a theoretical approach that explores the relationship between literature and the environment. This study is a qualitative study which analyzes data from the novel as its main source. The findings reveal some cases of environmental destruction, both biological and physical, caused by the use of modern technology, specifically in the context of warfare. This study underscores the importance of further research on environmental and war-related themes in literature, contributing to a broader understanding of global environmental issues.